2007
DOI: 10.1097/inf.0b013e3180f61708
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Cerebrospinal Fluid and Serum Cytokines in Patients With Kawasaki Disease

Abstract: The differences in the inflammatory cytokine value between CSF and serum suggest that the degree of systemic vasculitis is different between CSF and the circulating blood, and some patients with KD showed a higher degree of CSF inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
2
20
2
Order By: Relevance
“…11 However, KD is also characterized by multisystemic vasculitis and may thus affect blood perfusion and cause inflammatory changes in the brain. 12, 13 One study indicated that central nervous system (CNS) symptoms occur in 1-30 % of KD patients. 14 KD patients with CNS involvement may exhibit a variety of symptoms and signs, including irritability, lethargy, asep-…”
mentioning
confidence: 99%
“…11 However, KD is also characterized by multisystemic vasculitis and may thus affect blood perfusion and cause inflammatory changes in the brain. 12, 13 One study indicated that central nervous system (CNS) symptoms occur in 1-30 % of KD patients. 14 KD patients with CNS involvement may exhibit a variety of symptoms and signs, including irritability, lethargy, asep-…”
mentioning
confidence: 99%
“…Cerebrospinal fluid pleocytosis and increased cytokine levels, similar to those reported in encephalitis, are also observed in Kawasaki disease and reflect intracranial inflammation that is possibly responsible for the characteristic irritability 2 3. Predominantly neurological presentations of Kawasaki disease are well described and include focal cranial nerve palsies,4 encephalopathy5 and meningoencephalitis 6 7…”
mentioning
confidence: 74%
“…11 This was attributed to systemic vasculitis, but in a previous report, comparison of the cerebrospinal fluid of Kawasaki patients with that of controls manifesting acute encephalitis showed that these two groups had comparable levels of cytokines. 12 What is even more surprising is the elevated cerebrospinal fluid/serum cytokines ratio that some of the patients had, suggesting that the inflammatory process in the central nervous system is independent of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%